The Dissolution of the Monasteries in Sweden during the Reformation - Berntson, Martin (Religions, 2024)
This article discusses the dissolution of the monasteries in 16th century Sweden. The approximately fifty monasteries and friar’s convents that existed in Sweden in the early 16th century were all dissolved over a period of about eighty years. Decisive for this development were decisions during the Diet in Västerås 1527, which decreed that monasteries that depended on tax from their estates should be subordinated under a nobleman, and that the mendicant friars should not be allowed to travel outside their convents more than ten weeks each year. Whilst most of the monasteries inhabited by monks or brothers had been dissolved before the 1560s, four female houses were still in existence at this time. These remaining nunneries were supported financially by the state, possibly to safeguard the nuns’ social welfare. However, the monastic institutions were to meet a short-lived revival through the reign of King Johan III (rule 1568–1592), who not only supported them economically but also renovated a few of them and allowed Catholic priests to encourage Catholicism in Vadstena Abbey. Through this process of re-catholicizing, any prospects of creating successful Evangelical communities in Sweden were lost. The last remaining nunnery, Vadstena Abbey, was a vibrant Catholic institution when it was forced to close in 1595.